1979
DOI: 10.1080/09553007914551031
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Oxygen on the Survival and Yield of DNA Double-strand Breaks in Irradiated Yeast Cells

Abstract: Survival and induction of DNA double-strand breaks were studied in cells of Saccharomyces cerevisiae irradiated under oxic or anoxic conditions with 30 MeV electrons. A linear relationship between DNA double-strand breakage and dose was found in both cases. The o.e.r.-value for colony forming ability was found to be 1.9 +/- 0.2, whereas the o.e.r.-value for DNA double-strand breakage was 3.0 +/- 0.1. These results are not inconsistent with the idea that DNA double-strand breaks are involved in killing of yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…It has already been reported that in yeast the OER for induced dsb is 1.3 for e-particles (Frankenberg et al 1981) and 3.0 for sparsely ionizing 30 MeV electrons (Frankenberg-Schwager et al 1979). These data are in agreement with the low OERs generally observed for radiobiological endpoints at high LET.…”
Section: Discussionsupporting
confidence: 84%
“…It has already been reported that in yeast the OER for induced dsb is 1.3 for e-particles (Frankenberg et al 1981) and 3.0 for sparsely ionizing 30 MeV electrons (Frankenberg-Schwager et al 1979). These data are in agreement with the low OERs generally observed for radiobiological endpoints at high LET.…”
Section: Discussionsupporting
confidence: 84%
“…This strain, originally constructed by Brendel and F~ith (1974), is homozygous for the templ-3 marker conferring auxotropy for 2'-deoxythymidine (5'-dTMP) (Frankenberg-Schwager et al 1979). It is a petite lacking mitochondrial DNA and was generously given to us by Dr. M. Frankenberg-Schwager, G6ttingen, formerly GSF, Frankfurt.…”
Section: Yeast Strainmentioning
confidence: 99%
“…This observation suggests that DSB induction per base pair is approximately the same in the lower and higher eukaryotes. In yeast cells irradiated by 30 MeV electrons, the initial DSB yield per cell increases linearly with dose up to at least 2400 Gy under fully aerobic (100% O 2 ) conditions and up to at least 1500 Gy under maximally hypoxic conditions (17). The production of Fpg (oxidized purine), Endo III (oxidized pyrimidine) and Endo IV (abasic) non-DSB clusters is also proportional to absorbed dose for low-and high-LET radiations from at least 0.05 Gy up to 30 Gy (6,(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%